Knockdown Rab11‐FIP2 inhibits migration and invasion of nasopharyngeal carcinoma via suppressing Rho GTPase signaling. Issue 2 (26th August 2019) - Feng, Guofei; Qin, Liting; Liao, Zhipeng; Xiao, Xiling; Li, Bo; Cui, Wanmeng; Liang, Libin; Mo, Yingxi; Huang, Guangwu; Li, Ping; Zhou, Xiaoying; Zhang, Zhe; et al.
Abstract: Rab11 family interacting protein 2 (Rab11‐FIP2) is a conserved protein and effector molecule for the small GTPase Rab11. By interacting with Rab11 and MYO5B, Rab11‐FIP2 regulates endosome trafficking of plasma membrane proteins, promoting cellular motility. The endosomal trafficking system in nasopharyngeal carcinoma (NPC) remains unclear. Here, an outlier analysis using the Oncomine database suggested that Rab11‐FIP2 but not Rab11 and MYO5B was overexpressed in NPC. We confirmed that the transcription of Rab11‐FIP2 was upregulated in NPC cell lines and primary tumor tissues as compared with a normal nasopharyngeal epithelial cell line and normal nasopharynx tissues. We further confirmed the elevated protein expression level of Rab11‐FIP2 in NPC biopsies. Instead of regulating the epithelial‐mesenchymal transition or Akt signaling pathway, knockdown of Rab11‐FIP2 inhibited the migration and invasion ability of NPC cell lines by decreasing the expression of Rac and Cdc42. In summary, Rab11‐FIP2 could be an oncogene in NPC, mainly contributing to metastatic capacity by activating Rho GTPase signaling.